HUBUNGAN TERPAAN MEDIA TELEVISI DALAM PROGRAM DANGDUT ACADEMY DI INDOSIAR DENGAN PERSEPSI REMAJA DESA ANDONG KABUPATEN BOYOLALI - Prakoso, Ramadhan Aji; Siswanta, Maya Sekarwangi, (Solidaritas, 2017)
HUBUNGAN TERPAAN MEDIA TELEVISI DALAM PROGRAM DANGDUT ACADEMY DI INDOSIAR DENGAN PERSEPSI REMAJA DESA ANDONG KABUPATEN BOYOLALI Â Oleh:Ramadhan Aji PrakosoDra. Maya Sekarwangi, M.SiDrs. Siswanta, M.SiÂ Â AbstractThe purpose of this research is to find out the relations between media exposure of television on Dangdut Academy Program in Indosiar with adolescent perception. The type of research is explanatory research. Location of research in Andong Village Boyolali The population of this study is adolescent 15-19 years old in Andong village. Sampling technique used accidental sampling with sampel 70 adolescent. The data source uses primary data and secondary data. Techniques of collecting data used documentation, questionnaires and literature study. Data analysis technique used rank spearman correlation. The result of research with rank spearman correlation is obtained result of rs value of 0.607, where the value of correlation coefficient is positive so that there is relationship media exposure of television in Dangdut Academy program with adolescent perception at Andong Village Boyolali.. Keywords: media exposure, perception, adolescent